Characterization, performance evaluation and optimization of wheat straw – bagasse blended fuel pellets - Matasyoh, Isabel Musula; Osodo, Booker; Muguthu, Joseph; Kombe, Emmanuel (International Journal of Renewable Energy Development, 2024)
This study was carried out to assess the fuel pellets produced from wheat straw and sugarcane bagasse. The wheat straw and bagasse were blended into four ratios including; 10:90, 30:70, 70:30 and 90:10 (wheat straw: bagasse) and developed into fuel pellets. The fuel pellets were characterized to determine the moisture content, volatile matter, fixed carbon, ash content, calorific value, bulk density and mechanical durability. The ignition time, burning rate and specific fuel consumption of the wheat straw – bagasse blended fuel pellets were studied at varying blend ratios (10:90, 30:70, 70:30 and 90:10), moisture contents (9.1%, 10.6%, 12.6% and 14.7%) and raw material particle sizes (2 mm, 4 mm, 6 mm and 10 mm). Results indicated that the wheat straw: bagasse blend ratios containing more proportion of bagasse (30:70 and 10:90) recorded a shorter ignition time, higher burning rate and lower specific fuel consumption. Larger raw material particle sizes exhibited shorter ignition time, higher burning rate and specific fuel consumption. Moreso, the fuel pellets with low moisture contents also recorded shorter ignition time, higher burning rate and lower specific fuel consumption. It was concluded that fuel pellets with high quantity of bagasse, large particle sizes and low moisture content demonstrated favorable combustion characteristics. Response surface methodology was used in the optimization so as to determine the optimum combination of blending ratio, moisture content and raw material particle size that would result in the lowest ignition time, highest burning rate and lowest specific fuel consumption. Results indicated that an optimum combination of a wheat straw: bagasse blend ratio of 10:90, moisture content of 14.70% and a particle size of 10.00 mm resulted in the lowest ignition time, highest burning rate and lowest specific fuel consumption.